Semi-aerobic leachate treatment with powdered activated carbon addition to activated sludge process - Aghamohammadi, N. (2005)
Semi-aerobic leachate is characterized by organic matter (COD, BOD) which is relatively low in concentration and difficult to biodegrade. In conventional treatment systems, the low biodegradability is attributed to partial stabilization of leachate at the landfill. Biological treatment of leachate in Malaysia is not well established and any important data for the treatment process is not available. The behavior of microbes is unknown for semi aerobic leachate. This research will establish some of the important data in biological treatment with and without the influence of PAC. For the present study, semi aerobic leachate was collected from Pulau Burung Landfill Site (PBLS), Nibong Tebal, Penang. The experiment involved operating two 16 L bach laboratory-scale activated sludge reactors in parallel at room temperature. One of the reactors was supplemented with powdered activated carbon (PAC) to observe its effect on leachate biodegradation. The results showed enhanced reactor performance due to PAC addition; the colour and nitrogen ammonia removal was high and the sludge settleability was better.